Drug utilization pattern of antimicrobial agents in an outpatient department of otorhinolaryngology in a tertiary care hospital: a prospective, cross-sectional study - Sathiya, Sanket B.; Panchasara, Ashwin K.; Barvaliya, Manish J.; Jha, Sushil G.; Tripathi, C. B. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Study based on antimicrobial drug utilization pattern and focus on factors related to prescribing, administering and its associated events. The aim of this study is to assess the prescribing patterns of antimicrobials, to assess the appropriateness of prescribed antimicrobials in an ear, nose and throat (ENT) infections. Methods: A prospective observational drug utilization study was carried out in otorhinolaryngology department for a period of 4 months. Patients who attended the ENT outpatient department (OPD) with ENT infections were included in the study and patients who were not willing to participate in the study were excluded and the data were analyzed. Results: Out of 155 patients, the average number of drugs per patient was 1.2. The percentage of drugs prescribed with the generic name was 26.32%. During this study, it was found that the most commonly prescribed groups of antimicrobials were penicillins (34.87%) followed by fluroqinolones (26.32%) and nitroimidazole (25%). During the study, it was observed that 46.71% patients visited for treating ear infections, 12.5% for nasal infections and 40.79% for throat infections. The routes of administration were oral (74.23%) and topical (20.10%). Conclusions: Our study shows some rational prescription patterns like less utilization of antimicrobials in ENT infections and were according to standard treatment guideline. The results of this study will be useful in future for making standard treatment guidelines. It also promotes the rational prescription and rational use of drugs.